Management of risky adolescent sexual behaviour in rural secondary schools in Zimbabwe - Sibanda, Patrick (Pure and Applied Science Advances, 2018)
The study was aimed at examining methods and strategies used by rural secondary schools of Zimbabwe in managing risky adolescent sexual behaviour with the view of recommending more protective practices and improving on the existing ones. Literature is replete with cases of high incidences of risky adolescent sexual behaviours in schools in various countries and the need for methods for managing them thereof. The study utilized a mixed methods sequential explanatory research design with 200 teachers chosen using cluster sampling for the quantitative phase and 10 teachers purposively sampled for the qualitative phase of the study. The results of the study indicated that the most common risky adolescent sexual behaviours included premarital and unprotected sex, dating older partners and having multiple partners. Prostitution was also found to be causing concern, although it was not widespread. Corporal punishment was found to be the most dominant method used for managing risky adolescent sexual behaviour, although protective methods such as counselling, information dissemination, parental engagement and social academic supports were also used. Of note was that the positive or protective methods lacked precision in their practice. The schools had also to some extent established programmes such as Scripture Union (SU), Career Guidance and Counselling Clubs (CGCCs) and Sex Education programmes as means of combating risky sexual behaviour among adolescent students. They also used resource persons. However, these programmes were not well established and properly utilized. From the results, the study concluded that management of risky adolescent sexual behaviour in rural secondary schools of Zimbabwe was not premised on theoretically sound methods and programmes and was therefore bound to be ineffective. The study also concluded that girls were more predisposed to risky adolescent sexual behaviour than boys. The study then recommended in favour of training and awareness workshops as well as gender mainstreaming towards capacitating teachers in rural schools with skills and strategies for protective management of risky adolescent sexual behaviour.